2021
DOI: 10.1093/jalm/jfaa230
|View full text |Cite
|
Sign up to set email alerts
|

Gene Fusion Identification Using Anchor-Based Multiplex PCR and Next-Generation Sequencing

Abstract: Background Methods for identifying gene fusion events, such as fluorescence in situ hybridization (FISH), immunohistochemistry (IHC), and transcriptome analysis, are either single gene approaches or require bioinformatics expertise not generally available in clinical laboratories. We analytically validated a customized next-generation sequencing (NGS) panel targeting fusion events in 34 genes involving soft-tissue sarcomas. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Details of the Solid Tumor NGS fusion panel have been previously published 6–8 . Briefly, 5–10 unstained slides and one H&E‐stained slide from neutral buffered formalin‐fixed paraffin‐embedded tissue sectioned at 4 μm were obtained from each specimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the Solid Tumor NGS fusion panel have been previously published 6–8 . Briefly, 5–10 unstained slides and one H&E‐stained slide from neutral buffered formalin‐fixed paraffin‐embedded tissue sectioned at 4 μm were obtained from each specimen.…”
Section: Methodsmentioning
confidence: 99%
“…N G S Details of the Solid Tumor NGS fusion panel have been previously published. [6][7][8] Briefly, 5-10 unstained slides and one H&E-stained slide from neutral buffered formalin-fixed paraffin-embedded tissue sectioned at 4 lm were obtained from each specimen. cDNA libraries were made by the use of an anchored multiplex polymerase chain reaction (Archer FusionPlex standard protocol and reagents; Archer DX, Boulder, CO, USA) and custom-designed gene-specific primer pools, targeting the 59 genes included in this panel that are involved in bone and soft tissue (BST) tumours.…”
Section: P a T I E N T C O H O R T A N D D A T A C O L L E C T I O Nmentioning
confidence: 99%
“…Several previous studies on genetic mutation detection, including fusion genes in sarcoma, have been reported by NGS analysis using various genetic mutation detection panel kits. 13,17,[36][37][38][39] These studies have mainly reported data on fusion genes, genetic mutations, and gene amplification. Our current study obtained similar results for fusion genes.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the solid tumour NGS fusion panel were previously published 13 . Briefly, five to 10 unstained slides and one haematoxylin and eosin (H&E)‐stained slide from neutral buffered formalin‐fixed paraffin‐embedded (FFPE) tissue sectioned at 4 μm were obtained from each specimen.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the solid tumour NGS fusion panel were previously published. 13 Briefly, five to 10 unstained slides and one haematoxylin and eosin (H&E)-stained slide from neutral buffered formalin-fixed paraffinembedded (FFPE) tissue sectioned at 4 lm were obtained from each specimen. Slides were macrodissected and total nucleic acid (TNA) was extracted using the Maxwell â RSC RNA FFPE Kit (Promega, Madison, WI, USA, cat.…”
Section: M M U N O H I S T O C H E M I C a L S T A I N I N Gmentioning
confidence: 99%